Handbook of information exchange in supply chain management - Ha, Albert Y.; Tang, Christopher S. (Springer, 2017)
Sharing accurate and timely supply and demand information throughout a supply chain can yield significant performance improvements to all members of the supply chain. Despite the benefits, many firms are reluctant to share information with their supply chain partners due to an unequal distribution of risks, costs, and benefits among the partners. Thus, incentive mechanisms must be in place to induce communication, cooperation, and collaboration among all members of a supply chain. The issue of information exchange/sharing has been examined by various researchers over the last 15-20 years. However, there is no research book that compiles various approaches, analyses, key implications, as well as future development of this area. This book will serve as a handbook for researchers who are interested in learning the state of the art of the line of research in this area and explore open research topics in this area. Chapter authors, all leading researchers, have contributed 18 chapters broken into four distinct sections covering the Value of Information Sharing, Contracting and Information, Information Signaling, and Incentives for Information Sharing.
Keywords: Business logistics.; Business logistics -- Management.; Business communication -- Handbooks, manuals, etc.; elektronické knihy; electronic books